Integrasi Kearifan Lokal Papua melalui Pembuatan Makanan Ongol-Ongol dari Sagu dalam Pembelajaran IPAS di Kelas V Sekolah Dasar: Penelitian - Ardian Hangga Kelana; Tri Suwarningsih; Sakka Irawan; Nurwiati, Nurwiati; Marice Karubaba (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the integration of Papuan local wisdom through the activity of making ongol-ongol food from sago in Natural and Social Sciences (IPAS) learning in Grade V of SD Al-Ihsan Yapis Kotaraja. The research method used is a qualitative approach with a descriptive research type. The research subjects consisted of grade V teachers, grade V students, and the principal who participated in the learning process activities based on Papuan local wisdom. The data collection process through observation, interviews, and documentation. The results of the study indicate that the learning process of making ongol-ongol from sago can increase students' understanding of the material of changes in the state of matter, the concept of food, and increase a sense of pride in Papuan local wisdom. In addition, the implementation of the integration of Papuan local wisdom supports the learning of IPAS to be more contextual, meaningful, strengthens the character values ​​of mutual cooperation, and students' attitudes of responsibility. The integration of Papuan local wisdom through education is expected to be sustainable and developed in the IPAS learning process to create student learning experiences.